Adaptation of the Flipped Learning System to the B-Learning System - Silva, Osvaldo (2017)
The fb-learning system, presented in 2015, as shown in Cabral and Nunes (2015), now suffers one improvement that can be applied to all ways of teaching that have distant learning on its core. On this work, we suggest the needed adaptations in a b-learning system in order to its optimization using the fb-learning system. We work, as an example, with a solution that can be implemented in Azores, an archipelago of nine islands of Portugal, since these islands are an ideal laboratory to test different teachings solutions, due to the recent investments that the Regional Government is making on the use of new technologies in teaching. However, the results, strategies and methodologies will be easily applied in other places, or structures, where is needed to apply a broadcast system of teaching. The system itself is structured in a cooperative way, and by this way the organization of the system allows Education stakeholders deliver knowledge to isolated groups, or persons, if they cannot have the possibility to have physical presence in school, a face-to-face teacher, due to problems emerging from territory discontinuity, moments of political crisis, limited access from students due to physical limitations, budget limitations, and so many other situations that can occur and can cause a teaching disruption. Since the model can be adapted to any level of education, our concerns in this work are mainly directed to the analysis of the structure and methodologies when we combine the power of Technology with a modern way of long distance teaching.